Self-organised segregation of bacterial chromosomal origins - Hofmann, Andreas; Heermann, Dieter W. (bioRxiv beta, 2018)
In spite of much effort, many aspects of chromosome organisation and segregation in bacteria remain unclear. Even for Escherichia coli, the most widely studied bacterial model organism, we still do not know the underlying mechanisms. Like many other bacteria, the chromosomal origin of replication in E. coli is dynamically positioned throughout the cell cycle. Initially maintained at mid-cell, where replication occurs, origins are subsequently partitioned to opposite quarter positions. The Structural Maintenance of Chromosomes (SMC) complex, MukBEF, which is required for correct chromosome compaction and organisation, has been implicated in this behaviour but the mode of action is unknown. Here, we build on a recent self-organising model for the positioning of E. coli MukBEF, to propose an explanation for the positioning and partitioning of origins. We propose that a specific association of MukBEF with the origin region, results in a non-trivial feedback between the self-organising MukBEF gradient and the origins, leading to accurate positioning and partitioning as an emergent property. We compare the model to quantitative experimental data of origin dynamics and their colocalisation with MukBEF clusters and find excellent agreement. Overall, the model suggests that MukBEF and origins act together as a self-organising system for chromosome segregation and introduces protein self-organisation as an important consideration for future studies of chromosome dynamics.